Basic assessment of Portunus segnis (Forskål, 1775) – A baseline for stock management in the Western Arabian Gulf - Giraldes, Bruno Welter (2016)
Portunus segnis (Forskål, 1775) is the representative species of the Portunus pelagicus (Linnaeus, 1758) complex described as inhabiting the Arabian Gulf. It represents one of the most important decapod resources within this semi-enclosed hyper-saline and hyper-thermal marine eco-region. Previous biological and ecological descriptions for P. pelagicus (latu sensus) have focused on other Portunus species while P. segnis from the Arabian Gulf has remained undescribed. This is a matter of concern as without taxonomic and ecological descriptions a scientific baseline for standing stock management cannot be created. In order to collate comprehensive baseline data for P. segnis vital biological, ecological and taxonomic information was examined and those results can be used to form the basis of a management strategy for this species within the Arabian Gulf. The research combines an overview of local unpublished works and new information about morphometric relations, body size ratios, size maturity, mortality, fecundity, spawning, recruitment, growth, sex ratio, sex dimorphism, colour pattern, habitat, taxonomy and discussion about the effects of temperature and salinity on this species.